Discrete dislocation dynamics simulations in a cylinder. Issue 1 (17th February 2015) - Li, Maosheng; Gao, Chan; Xu, Jianing
Abstract: Mechanical properties of material are closely related to the motion of dislocations, and predicting the interactions and resulting collective motion of dislocations is a major task in understanding and modelling plastically deforming materials. A discrete dislocation dynamics model is used to describe the orientation substructure within the microstructure. Discrete dislocation dynamics simulations in three dimensions have been used to examine the role of dislocation multiplication and mobility on the plasticity in small samples under uniaxial compression. In this paper we describe the application of the dislocation dynamics simulations in a cylindrical geometry. The boundary conditions for the simulation were estimated from the distribution of the geometrically necessary dislocation density which was obtained from the orientation map. Numerical studies benchmark could validate the accuracy of the algorithms and the importance of handling the singularity correctly. The results of the simulation explain the formation of the experimentally observed substructure.